Prevalence of prolonged grief disorder and its symptoms in Chinese parents who lost their only child: A systematic review and meta-analysis - Yuan, Meng-Di; Wang, Zong-Qin; Fei, Lei; Zhong, Bao-Liang (Frontiers in Public Health, 2022)
Background: Parents who lost their only child and cannot have a second child (“Shidu”) have been a large population in China. Prolonged grief disorder (PGD) in Shidu parents is of clinical and public health concern but the reported PGD prevalence varies widely. To facilitate the planning of grief counselling services, this meta-analysis estimated prevalence of PGD and its symptoms and identified subgroups at elevated risk for PGD. Methods: We searched English and Chinese literature databases to identify cross-sectional surveys reporting prevalence of PGD or PGD symptoms in Chinese Shidu parents. The Joanna Briggs Institute Critical Appraisal Checklist for Studies Reporting Prevalence Data (“JBI”) was used to assess risk of bias of included studies. Results: Seven studies with a total of 2794 Shidu parents were included and their JBI scores ranged from five to eight. The pooled prevalence of PGD and PGD symptoms was 20.9% and 75.0%, respectively. Greater risk of PGD was observed in mothers (vs. fathers, OR [odds ratio] =1.89, P=0.001) and in parents with religious beliefs (vs. without religious beliefs, OR=1.65, P=0.040). More severe PGD symptoms were presented in parents whose only child died from accidents (vs. illness, MD [mean difference] =3.99, P<0.001). Deceased children of PGD parents were older than those of non-PGD parents (MD=1.64, P=0.035) and PGD parents had a shorter duration since the loss than non-PGD parents (MD=-3.26, P=0.013). Conclusions: PGD is prevalent among Shidu parents. Grief counselling services for Shidu parents would be more effective if they target those who are mothers and have religious beliefs and those whose children died from accidents, lost children are older, and loss occurs more recently.